Integrating Science and Islamic Values Through Excellence Programs in Pesantren Education - Muhammad Suwignyo Prayogo; Sutiah; M. Fahim Tharaba (MUMTAZ : Jurnal Pendidikan Agama Islam, 2025)
This study addresses the limited empirical explanation of how Islamic educational institutions operationalize the integration of science and Islamic values in practice. It aims to examine how excellence programs in pesantren education facilitate this integration within daily learning processes. A qualitative case study was conducted at Pesantren Nurul Islam Jember, Indonesia. Data were collected through in-depth interviews with key stakeholders (pesantren leader, madrasah head, program coordinator, teachers, mentors, and students), classroom and laboratory observations, and analysis of institutional documents. Data were analyzed using an interactive model consisting of data condensation, data display, and conclusion verification. The findings reveal that the science excellence program functions as an integrative platform through four key components: institutional commitment, reflective pedagogy, collaborative learning, and experiential activities (e.g., robotics and competition-based mentoring). These components not only improve students’ scientific competencies and academic achievements but also foster discipline, ethical awareness, and leadership within a pesantren-based learning culture. This study concludes that excellence programs provide a practical and context-specific model for integrating science and Islamic values in Islamic education. The study contributes empirically by demonstrating how institutional programs translate integrative educational ideals into everyday practices.